Síntese de partículas submicrométricas de carbonato de cálcio a partir de sais inorgânicos utilizando polímeros lineares como modificadores de cristalização - Facchinetto, Sara Elisa (2017)
In this work, we report the synthesis of submicrometer calcium carbonate particles using the simplest approach of mixing solutions of calcium chloride and ammonium carbonate inorganic precursors in presence of crystallization modifiers. The typical crystallization of CaCO3 into large calcite crystals with rhombohedral morphology changed to very small (down to 0.8 μm) uniform spherical vaterite particles upon addition of small amounts (0.01 to 2.00 mg/mL) of the anionic homopolymer poly(sodium 4-styrenesulfonate) (PSS).The reaction temperature must be preferably kept low around 25 °C. Heating induces the formation of an unstable hydrated phase, which is quickly converted back to the most stable structure, however with some broadening in the particle size distribution. In contrast, large spheres made of a collection of calcite polycrystallite aggregates formed in presence of poly(acrylic acid) (PAA) under otherwise the same experimental conditions. Crystal growth in a preorganized environment created by selective distribution of Ca(II) ions onto the shell of polyestyrene-b-poly(acrylic acid) (PS-b-PAA) core-shell spherical micelles revealed a rather poor control of size and morphology. Therefore, PSS anionic homopolymer can be applied to the synthesis of submicrometer CaCO3 particles from solutions of inorganic salts, which is a much cheaper and sustainable method than controlled CO2 gas production and diffusion. Representative polymer@CaCO3 particle systems were used to prepare PCL-based composites, of which the rheological behavior was accessed by oscillatory rheology.